The Main Issues in the Application of RFAI: a perspective on recent arbitral decisions - FERNANDES, Ana; TABORDA, Daniel; MARTINS, António (Revista Jurídica Portucalense, 2025)
The application of RFAI generates considerable litigation. At the arbitration courts (CAAD), 43 cases were decided in 2024. Of the 33 cases relevant for our analysis, the main points of conflict between the Tax Authority and taxpayers are the eligibility of the economic activity, job creation, and the increase in production capacity. This text seeks to identify the controversial issues within these three categories by analyzing the arguments presented by the Tax Authority and by the taxpayers, as well as the legal and economic rationale behind the respective court decisions.